Documents and Archives in Early America - Jimerson, Randall C. (Archivaria, 2006)
Concern for documents and archival records in America began with religious motives and concern for colonists’ rights. By the late 18th century historians increasingly relied on original documents to establish facts and “objective” truth. Beginning with the Revolution historical documents served patriotic and nationalistic purposes, such as veneration of heroes. Efforts to preserve irreplaceable documents resulted in two separate but closely linked traditions – “multiplying the copies” through documentary editing and publication, and establishing repositories to protect original documents. This marked the beginning of archival consciousness in America, led by private historical societies. Archives served the needs of the social elite and confirmed their power. RÉSUMÉ L’intérêt pour les documents d’archives en Amérique est né de motifs religieux et d’une préoccupation pour les droits des colons. Vers la fin du 18e siècle, les historiens s’appuyaient de plus en plus sur les documents originaux pour établir les faits et la vérité « objective ». À partir de la Révolution, les documents historiques servaient des buts patriotiques et nationalistes, comme le culte des héros. Deux traditions différentes mais complémentaires résultent des efforts pour préserver les documents jugés irremplaçables : la multiplication de copies par l’édition et la publication, et l’établissement de dépôts afin de protéger les documents originaux. On assiste alors au début de la conscience archivistique en Amérique, menée par des sociétés historiques privées. Les archives servent alors les besoins de l’élite sociale et confirment leur pouvoir.